Urgensi Materi Khatib Jum’at Kyai-Kyai Kampung sebagai Upaya Gerakan Deradikalisasi Agama di Kabupaten Kediri - Muslim, Ahmad Shobiri (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
The aims of the research is to determine the influence of khutbah jum’at material of some Islamic leaders in the several villages of Kediri-East Java in the role in minimizing the radicalism of Islam. This study includes field research based on several supporting data of observation, including; interview, participation and trining which is coverage around three mounths in the some villages on 7 districts of Kediri regency. Therefore, by analyzing the role of some Islamic leader (read; kyai) in the some Kediri villages, this research encourages that they have a so big potential in the process of giving a religious understanding to their community to minimize radicalism in Islam. This project tries to explain the role of kyai in the village is so significan in the process of de-radicalism (minimizing radicalism in Islam). The goal of this research is a finding that this potential of kyai in the some villages-Kediri should be organized and supported by several sides including; government, academic institution, and others. Hopefully, this research would like to really give a massive contribution in the process of religious radicalism in Kediri specially, and Indonesia universally.